Role of the triple helix in the ecosystems for tech start-ups in India: a gap analysis. (6th March 2019) - Subrahmanya, M.H. Bala
Tech start-ups and their entrepreneurial ecosystems are assuming increasing global attention, particularly from policy makers and empirical researchers, alike. If entrepreneurial ecosystems have to be promoted for an accelerated birth and growth of tech start-ups, it is imperative to understand its structure, essential components and the gaps, if exist. Against this backdrop, this article attempts to ascertain the gap between an ideal ecosystem and the prevailing ecosystems and its causal factors, based on four-stage interactions with ecosystem stakeholders (by means of Delphi technique application) in Bangalore and Hyderabad, in India. The gap analysis is done by means of a hierarchical regression model for five different sets of components of the ecosystem structure, apart from a control (dummy) variable to distinguish Bangalore from Hyderabad. The hierarchical regression analysis substantiated the entrepreneurial ecosystem structure for tech start-ups proposed in terms of relative importance of various sets of components, and ascertained the factors responsible for the ecosystem gap.